The impact of knowledge vacuum to innovation process during public research organizations merger - Kirana Rukmayuninda Ririh; Elisa Anggraeni; Machfud Machfud; Nurul Taufiqu Rochman (Serbian Journal of Management)
Maintaining innovation process during merger in a merged public research organization is quite a challenge. Knowledge vacuum is a potential rising issue due to merger. This study aims to examine knowledge vacuum as intervening role between organizational factors and individual factor, also how it impacts the innovation process. PLS-SEM is applied by using software SmartPLS 4.0, and 198 innovation actors are involving in questionnaires survey. Surprisingly, the results show that knowledge vacuum positively and significantly influences absorptive and adaptive capability to form distinctive competencies. It shows that missing knowledge flows among high-performer actors, such as innovators, will enhance competencies during chaotic event due to merger. In addition, distinctive competencies have a significant positive influence to innovation process. On the other hand, knowledge vacuum is not having a direct relationship to distinctive competencies. Resource and infrastructure management has a contribution to positively forming knowledge vacuum during merger to create strong absorptive and adaptive capability and curve prominent distinctive competencies, which eventually will positively impact the innovation process.